Peran Pendidikan Dalam Membangun Sikap Moderasi Beragama Di Kalangan Mahasiswa - Chilmi Khoirun Nisa; Neng Sifa Aliya Putri; Ilham Hasanudin; Fiqra Muhamad Nazib (Yayasan Al-Afif, 2025)
Indonesia, as a country with high religious and cultural diversity, faces challenges in building attitudes of religious moderation among students. Religious moderation, which includes tolerance, balance and respect for differences, is needed to prevent radicalism and conflict between religious believers. This research uses the Systematic Literature Review (SLR) method to evaluate the role of higher education in integrating the values of religious moderation through curriculum, learning, and religious moderation in higher education. The results of the study show that the hidden curriculum-based curriculum, integration of multicultural education, and courses such as Pancasila Education and Comparative Religion Science are effective in building students' moderate character. Implementation of the values of religious moderation is also carried out through Islamic Religious Education learning which emphasizes morals and teacher examples. Examples of implementation in several universities show the importance of principles such as deliberation, tolerance and inclusive attitudes in creating a harmonious academic environment.